Contrasting charge-carrier dynamics across key metal-halide perovskite compositions through in situ simultaneous probes - Ulatowski, AM; Elmestekawy, KA; Patel, JB; Noel, NK; Yan, S; Kraus, H; Huggard, PG; Johnston, MB; Herz, LM (Wiley, 2023)
Metal-halide perovskites have proven to be a versatile group of semiconductors for optoelectronic applications, with ease of bandgap tuning and stability improvements enabled by halide and cation mixing. However, such compositional variations can be accompanied by significant changes in their charge-carrier transport and recombination regimes that are still not fully understood. Here, a novel combinatorial technique is presented to disentangle such dynamic processes over a wide range of temperatures, based on transient free-space, high-frequency microwave conductivity and photoluminescence measurements conducted simultaneously in situ. Such measurements are used to reveal and contrast the dominant charge-carrier recombination pathways for a range of key compositions: prototypical methylammonium lead iodide perovskite (MAPbI3), the stable mixed formamidinium-caesium lead-halide perovskite FA0.83Cs0.17PbBr0.6I2.4 targeted for photovoltaic tandems with silicon, and fully inorganic wide-bandgap CsPbBr3 aimed toward light sources and X-ray detector applications. The changes in charge-carrier dynamics in FA0.83Cs0.17PbBr0.6I2.4 across temperatures are shown to be dominated by radiative processes, while those in MAPbI3 are governed by energetic disorder at low temperatures, low-bandgap minority-phase inclusions around the phase transition, and non-radiative processes at room temperature. In contrast, CsPbBr3 exhibits significant charge-carrier trapping at low and high temperatures, highlighting the need for improvement of material processing techniques for wide-bandgap perovskites.